Evaluating the financial performance according to the traditional and modern financial indicators - Mokhalad Hamzah Jaddoa, Manal Hameed Majeed, Amal Noori Mohammed (Opción, 2019)
The research aims to develop the general performance and improve the level of activity of private insurance companies in line with the current progress of the country via qualitative and quantitative comparative research methods. The results of the research show a great interest from the side of the management of companies in this concept. The research concluded that the added economic value is a broad concept that goes beyond the traditional performance evaluation process and is based on compound costs related to the cost of debt, the weighted average cost of capital and the profits realized.